Knowledge sharing from the perspective of Middle Eastern doctoral students studying at a Malaysian Islamic university - Sadeq, Abdallah I A; Mhd. Sarif, Suhaimi; Juhdi, Nurita; Abdul Hamid, Zabeda (International Open University (IOU), 2023)
People have many reasons to further their studies in foreign countries. One of the prominent reasons is to gain knowledge and experience that might be lacking in their homeland. The other major reason is to share knowledge with others. The purpose of this research is to explore the views on knowledge sharing among university students. Five doctoral students from five Middle Eastern countries studying in an Islamic university in Malaysia were interviewed to get their views on knowledge sharing. The researcher analysed the responses from the interviews using inductive thematic analysis. From the analysis, fifty-seven (57) codes were obtained and later they were reduced into eleven (11) categories and finally resulted in four (4) major themes: concepts, importance, process, and factors influencing knowledge sharing. The findings showed that all five respondents have almost similar views on the knowledge-sharing concepts and importance. On the knowledge-sharing process, they posited the need to have the eco-system (bi’ah) in the university that facilitates the process. Factors that influence knowledge sharing include the university ecosystem (bi’ah), financial resources, aptitude, cultural diversity, and political stability. The results of this study will help universities to determine what they should focus on to increase knowledge-sharing while creating the appropriate environment and to raise the reputation of the universities. This is also in line with Sustainability Development Goal number 4 (Quality Education). Most importantly, the findings will contribute vehemently to the Muslim nations